“I Doubt If They Were Unusual”: Race and Place in Helen Creighton’s 1967 African Nova Scotian Recording Project - Greencorn, Chris (MUSICultures)

(untitled) (Canadian Society for Traditional Music / La Société canadienne pour les traditions musicales, 2024)
Helen Creighton (1899–1989) was one of Canada’s foremost folk song collectors and folklorists. Her fieldwork, which spanned the late 1920s to the mid- 1960s, centred on her home province of Nova Scotia. This article critically examines Helen Creighton’s 1967 recording project in African Nova Scotian communities, particularly in the historic settlement of Africville during its notorious displacement by the city government of Halifax. Despite receiving little attention in the half-century since, the 1967 project offers considerable insight into the place of race and racialization in Creighton’s influential conception of Nova Scotian folk culture. I argue that Creighton observed a double standard around the authenticity of the African Nova Scotian songs she collected vis-à-vis those collected in white communities, and that this inequitable treatment was intrinsically connected to the rhetorical and physical displacement of African Nova Scotians that underwrote her project.